A quantum secret sharing scheme on access structure. (17th February 2016) - Qin, Huawang; Zhu, Xiaohua; Dai, Yuewei
Abstract : Based on the Einstein-Podolsky-Rosen (EPR) entangled state and the unitary operation, a quantum secret-sharing (QSS) scheme on access structure is proposed. The participants randomly choose their private keys themselves. Each participant keeps one private key even though he belongs to several qualified subsets. In the recovery, the participants in the qualified subset perform the unitary operations on the EPR pairs, and recover the secret through the Bell-state measurement. Compared to the existing QSS schemes on ( n,   n ) or ( t,   n ) structure, the proposed scheme on access structure is more flexible in practice.